Removal of Cd2+ from aqueous solution using graphene oxide modified activate carbon derived from peanut shell - Du, Yilu; Wang, Hui; Ji, Jiangtao; Jin, Xin; Song, Yang; Zhang, Hao; Chen, Zhi (International Journal of Agricultural and Biological Engineering, 2023)
Graphene oxide (GO) was prepared by a modified Hummers method using peanut shells and natural graphite, and graphene oxide modified peanut shells activated carbon composites (GO-AC) were synthesized by co-pyrolysis. The optimal preparation conditions of AC were screened by response surface methodology (RSM) to optimize the preparation process. The results showed that the surface of GO-AC had more micropores and larger specific surface area, increased the surface adsorption sites and had more oxygen-containing functional groups. The adsorption process was mainly based on chemisorption, and the adsorption capacity was 3.45 and 1.30 times higher than that of BC (45.16 mg/g) and AC (119.21 mg/g), respectively. After six adsorption-desorption cycle tests, the adsorption amount of Cd2+ by GO-AC was still as high as 89.26 mg/g, with a percentage increase of 93.5% and 365% compared to BC (19.18 mg/g) and AC (46.13 mg/g), respectively, with good reusability. The research can provide a useful reference for the high value-added conversion of waste biomass, and GO-AC loading modified with significant adsorption of Cd2+ has good potential for application as a novel and low-cost adsorbent.Keywords: graphene oxide-modified biochar, response surface optimization, adsorption, heavy metalDOI: 10.25165/j.ijabe.20231605.8046Citation: Du Y L, Wang H, Ji J T, Jin X, Song Y, Zhang H, et al. Removal of Cd2+ from aqueous solution using graphene oxide modified activate carbon derived from peanut shell. Int J Agric & Biol Eng, 2023; 16(5): 226–235.